Analisis Daya Dukung Wisata dalam Mendukung Konsep Pariwisata Berkelanjutan di Kebun Raya Bogor - Imam Ardiansyah; Felicia Tandi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2023)
The purpose of this research is about the carrying capacity of tourism and its impact in relation to managing sustainable destination development so that it leads to environmental conservation. This research method uses primary and secondary data obtained from the results of questionnaires by tourists and interviews with management. The technique for taking samples is by non-probability sampling. The results showed for 1) tourists' perceptions of facilities at the Bogor Botanical Gardens such as food courts, parking lots, accessibility, toilets, places of worship, souvenir shops, information counters, directions, seats, cleanliness and security with an average value of 4.12. in the GOOD category, 2) for the carrying capacity of the area for weekdays the carrying capacity ratio is still below 30% of the maximum threshold and for weekends and holidays the carrying capacity ratio is between 70% - 90% of the maximum capacity of the Bogor Botanical Gardens of 28,554 tourists, 3) Land Suitability Index for tourism activities in the Bogor Botanical Gardens from the results that this area is classified as VERY APPROPRIATE (S1) with an index value of 90% which means that land suitability for tourism activities has a high level of feasibility. Suggestions are given to managers to pay attention to the capacity of tourists in accordance with the carrying capacity of the area to be used as a strategic basis for future tourism development.